2014
DOI: 10.4251/wjgo.v6.i4.83
|View full text |Cite
|
Sign up to set email alerts
|

Use of blood-based biomarkers for early diagnosis and surveillance of colorectal cancer

Abstract: Early screening for colorectal cancer (CRC) holds the key to combat and control the increasing global burden of CRC morbidity and mortality. However, the current available screening modalities are severely inadequate because of their high cost and cumbersome preparatory procedures that ultimately lead to a low participation rate. People simply do not like to have colonoscopies. It would be ideal, therefore, to develop an alternative modality based on blood biomarkers as the first line screening test. This will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 146 publications
0
52
0
1
Order By: Relevance
“…This indicated that microRNAs play an important role in the pathophysiology of disease (Ai et al, 2010). At present, numerous microRNAs have already been found in serum through the application of high-throughput sequencing, and these are widely used in clinical diagnosis and in the determination of prognosis of tumors and other diseases (Ganepola et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that microRNAs play an important role in the pathophysiology of disease (Ai et al, 2010). At present, numerous microRNAs have already been found in serum through the application of high-throughput sequencing, and these are widely used in clinical diagnosis and in the determination of prognosis of tumors and other diseases (Ganepola et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore an unmet need for an effective and routine test for asymptomatic average-risk individuals. A blood-based test is highly attractive due to its minimal invasiveness, convenience, and high acceptance by individuals at average risk (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…NGS is not only fast and cheaper but it also enables researchers to perform direct RNA sequencing (RNA-seq) to sequence the whole transcriptome (ie, the entire set of coding and noncoding RNAs). 44 mRNA Markers: In a proof-of-concept study, Tsouma et al 45 demonstrated that extracted carcinoembryonic antigen (CEA), cytokeratin 20, and epidermal growth factor receptor (EGFR) transcripts from patients with CRC can indicate disease stage and prognosis.…”
Section: Rna Markersmentioning
confidence: 99%
“…48 miR-17-3p, miR-92, miR-92a, miR-29a, miR-141, and miR-21 have been associated with advanced CRC and poor prognosis. 44,49 miR-21 expression levels may be a special pan-cancer marker, because it has been shown to be upregulated in other cancers. 50 miR-15b, miR-17-3p, miR-18a, miR-20a, miR-21, miR-29a, and miR-92a have been studied by multiple investigators for CRC detection.…”
Section: Rna Markersmentioning
confidence: 99%
See 1 more Smart Citation